Brassinosteroid biosynthesis gene OsD2 is associated with low-temperature germinability in rice - Kim, Sun Ha; Shim, Kyu-Chan; Lee, Hyun-Sook; Jeon, Yun-A; Adeva, Cheryl; Luong, Ngoc Ha; Ahn, Sang-Nag (Frontiers in Plant Science, 2022)
In rice, low-temperature germinability (LTG) is essential for stable stand establishment using the direct seeding method in temperate and high-altitude areas. Previously, we reported that the quantitative trait locus qLTG1 is associated with LTG. qLTG1 is also associated with tolerance to several abiotic stresses, such as salt and osmotic conditions. In this study, map-based cloning and sequence analysis indicated that qLTG1 is allelic to DWARF2 (OsD2), which encodes cytochrome P450 D2 (LOC_Os01g10040) involved in brassinosteroid (BR) biosynthesis. Sequence comparison of the two parental lines, Hwaseong and Oryza rufipogon (IRGC 105491), revealed five single nucleotide polymorphisms (SNPs) in the coding region. Three of these SNPs led to missense mutations in OsD2, whereas the other two SNPs were synonymous. We evaluated two T-DNA insertion mutants, viz., overexpression (OsD2-OE) and knock-down (OsD2-KD) mutants of OsD2, with the Dongjin genetic background. OsD2-KD plants showed a decrease in LTG and grain size. In contrast, OsD2-OE plants showed an increase in grain size and LTG. We also examined the expression levels of several BR signaling and biosynthetic genes using the T-DNA insertion mutants. Gene expression analysis and BR application experiments demonstrated that BR enhanced the seed germination rate under low-temperature conditions. These results suggest that OsD2 is associated with the regulation of LTG and improving grain size. Thus, OsD2 may be a suitable target for rice breeding programs to improve rice yield and LTG.